Reverse-Phase High-Performance Liquid Chromatography (HPLC) Analysis of Retinol and Retinyl Esters in Mouse Serum and Tissues - Kim, Youn-Kyung (2010)
The ability to measure endogenous metabolites of retinoids (vitamin A and its derivatives) in biological samples is key to understanding the crucial physiological actions of vitamin A. Over the years, many assays and methods have been developed to analyze different retinoids in biological samples. Liquid chromatography is the best analytical technique for routine analysis of these compounds. However, due to their different chemical properties, different retinoid metabolites cannot be accurately separated and quantified in a single chromatographic run. Here, we will describe a reverse-phase HPLC isocratic method that enables extraction, separation, identification, and quantification of all-trans-retinol and different molecular species of retinyl ester with high accuracy, sensitivity, and reliability.